Habitat and Distribution Modeling of Prehistoric Hippos (Hippopotamus sivalensis spp.) During Pleistocene in Java Island - Andriwibowo, Andriwibowo; Basukriadi, Adi; Nurdin, Erwin (Jurnal Biodjati, 2021)
Currently, there are only 2 extant species of hippos including common (Hippopotamus amphibius) and pygmy hipposÂ (Choeropsis liberiensis)Â . But in prehistoric times, there were several species. During Â Pleistocene theseÂ species wereÂ known to migrate to Java Island from Asian ContinentÂ and the species was Hippopotamus sivalensis spp. In this regard, this study aimedÂ to model the habitatÂ of H. sivalensis spp., ecology,Â and biodiversity of Hippopotamus sivalensis spp. based on the fossil record. The model was developed based on the Principal Component Analysis (PCA) methodÂ using the R statistical package. The results showed that there were 7 populations of H. sivalensis spp. that livedÂ at various altitudes with an average of 177 m above sea level (95% CIÂ : 123-232 m). According to PCA, there wereÂ at least 2 separate populations of H. sivalensis spp. One population occupies the forest while another occupies a habitat close to the coast. Currently the habitat for H. sivalensis spp. already changed. Based on habitat modeling, H. sivalensis spp. inhabit streams with submerged aquatic plants and shrubs and trees growing alongÂ river banks.